China at the Threshold of a Market Economy - Bell, Michael (Occasional Papers; Occasional Paper ;, 1993)
This paper reviews China's experience with market-oriented reform since 1978, including domestic reforms, the opening of the economy to foreign trade and investment, and the decentralization of decision making. It identifies special conditions that may have affected China's capacity to implement reforms, assesses the impact of the reforms on the structure of the economy and on its integration into the world economy, examines the effect of the reforms on macroeconomic management and stability, and draws implications for the direction of China's future reform strategy.